2021
DOI: 10.1021/acs.jafc.1c00724
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein Attenuated Arsenic-Induced Cytotoxicity: The Underlying Mechanism Reflected by Metabolomics and Lipidomics

Abstract: Arsenic ions (As3+) have been recognized as a hazard that threatens the health of humans. Metallothionein (MT) rich in cysteine may provide favorable binding sites for chelation of As3+. However, the influence of MT on As3+-induced toxicity and the underlying mechanism are poorly understood, especially at the metabolic level. Herein, the effects of MT on As3+-induced toxicity were evaluated. Cell viability analysis suggested that MT alleviated As3+-induced cytotoxicity. The metabolic response of PC12 cells to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…48 Moreover, it plays an essential role in the glucose−alanine cycle in tissues and the liver in mammals. 39 The increased alanine levels were downregulated in the UVB-FX-treated group compared to that in positive control cells, demonstrating the antioxidative potential of FX. 49 Asparagine, an important amino acid regulator, is involved in multiple metabolic processes, including amino acid homeostasis, nucleotide synthesis, and cell proliferation.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…48 Moreover, it plays an essential role in the glucose−alanine cycle in tissues and the liver in mammals. 39 The increased alanine levels were downregulated in the UVB-FX-treated group compared to that in positive control cells, demonstrating the antioxidative potential of FX. 49 Asparagine, an important amino acid regulator, is involved in multiple metabolic processes, including amino acid homeostasis, nucleotide synthesis, and cell proliferation.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…The phospholipid bilayer and its associated lipids are the major part of the cellular membrane, existing as primary targets of ROS attack, which can easily leads to lipid peroxidation. 39 Levels of most PC lipids, including PC(13:0), PC(14:0), PC(15:0), PC(16:0), PC(16:1), and PC(22:1), were significantly reduced in cells in the positive control group but upregulated after incubation with FX. Moreover, the levels of PE, PI, PG, and PS were similarly restored in the UVB-FX-treated group, while LPC and LPE were downregulated compared with their abundance in the positive control group (Figure S4).…”
Section: ■ Results and Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Moreover, they might play a relevant function as ROS scavengers. Recently, it was proven that MTs can chelate As(III) in human cells [146], although many previous reports suggested this property [147][148][149][150]. In silico genomic analysis showed that MT genes are well represented in diverse groups of microalgae, but they are scarce in diatoms and dinoflagellates, two important groups of primary production in marine environments.…”
Section: Biotransformation and Resistance/tolerance To As In Fungi And Protistsmentioning
confidence: 99%